IMPLEMENTASI PERATURAN MAHKAMAH AGUNG NO. 3 TAHUN 2017 TENTANG PEDOMAN MENGADILI PERKARA PEREMPUAN BERHADAPAN DENGAN HUKUM TERHADAP PERKARA CERAI GUGAT DI PENGADILAN AGAMA TANJUNG KARANG - Rizky Silvia Putri dan Amar Ma’ruf (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2018)
Women have the right to treatment in every problem that is being faced, in terms of solving women’s problems, must be balanced with the existence of justice in its implementation, because justice itself is an effort to protect women from male discrimination or groups who judge that women only as weak creatures. All people are equal before the law and are entitled to the same legal protection without discrimination, the sentence is a basic principle in law and human rights. Protection and certainty of law that is fair and equal treatment before the law is also one of the things guaranteed in the Constitution of the Republic of Indonesia as regulated in article 28 letter D paragraph (1). This study discusses the Implementation of Peraturan Mahkamah Agung No. 3 of 2017 concerning Guidelines for Judging Women’s Cases in Confronting Laws Against Divorce Cases in Tanjung Karang Religious Court. This research is research (field research) with primary data that is data obtained from the first source, in this study the primary data are the results of interviews, observations and documentation results. The results of this study that the implementation of the Peraturan Mahkamah Agung No. 3 of 2017 concerning Guidelines for Judging Women’s Cases in Confronting Law Against Divorce Cases in Tanjung Karang Class 1A Religion Court is still very minimal, it can be proven by the absence of a divorce case decision with a gender perspective.